Relative value of ruminally degradable and undegradable protein on the utilization of low-quality prairie hay by steers - Wickersham, T.A.; Cochran, R.C.; Farmer, C.G.; Klevesahl, E.A.; Arroquy, J.I.; Johnson, D.E.; Gnad, D.P.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was performed to investigate the impact of providing six levels of ruminally degradable protein (RDP; protein that is available to ruminal microbes) in combination with two levels of ruminally undegradable protein (RUP; protein that is not available to the ruminal microbes, but can be digested directly by cattle) on the intake and digestion of low-quality prairie hay. Twelve steers were provided unlimited access to low-quality prairie hay (5.3% crude protein and 71.7% neutral detergent fiber) throughout the trial. To simulate dietary RUP, casein was infused abomasally once daily at either 0 or 0.087% of body weight. To simulate dietary RDP, casein was infused ruminally once daily at 0, 0.029, 0.058, 0.087, 0.116, or 0.145% of body weight. As provision of RDP increased, forage intake and fiber digestion increased. Supplementing with RUP alone increased forage intake but not fiber digestion, although the intake response was not as large as providing the same amount of RDP. In conclusion, RUP is less efficient than RDP in stimulating forage intake and digestion.
Keywords: Beef; Rumen; Undegradable protein; Low-quality prairie hay; Steers